Polyphenolic compounds with anti-tumour potential from Corchorus olitorius (L.) Tiliaceae, a Nigerian leaf vegetable. Issue 15 (1st August 2016) - Taiwo, Bamigboye J.; Taiwo, Grace O.; Olubiyi, Olujide O.; Fatokun, Amos A.
Graphical abstract: Abstract: Chromatographic fractionation of the methanolic extract of Corchorus olitorius (L.) (Tiliaceae), on silica gel yielded two polyphenolic compounds. The structures of the compounds were elucidated as Methyl-1, 4, 5-tri- O -caffeoyl quinate and trans -3-(4-Hydroxy-3-methoxyphenyl)acrylic anhydride, based on extensive use of spectroscopic techniques such as 1 H and 13 C NMR, DEPT and 2D NMR experiments (COSY, HSQC, HMBC), IR and MS. To establish an initial proof-of-concept for the biological relevance of these compounds, their cytotoxicity against the cancer cell lines HeLa, HL460 and PC3, which might indicate their anti-tumour potential, was assessed. The compounds when tested at a range of concentrations up to 1.6 mM were found to possess mild cytotoxic activity which was significant against HeLa cells at ⩾800 μM. The trans -3-(4-Hydroxy-3-methoxyl phenyl)acrylic anhydride was found to be related to curcumin, a compound known to have anti-cancer activity. Docking of each of the two compounds and also of curcumin into some molecular targets implicated in tumourigenesis revealed that the three compounds had binding affinities that were superior to those obtained for the co-crystallized inhibitors of metalloproteinase-9, fibroblast growth factor receptor 2 (FGFR2) and epidermal growth factor receptor (EGFR). The plant Corchorus olitorius therefore represents a potential source of natural 'lead' compounds with anti-tumour potential.